Filiaç\~ao sindical de trabalhadores no Brasil (2012-2022): Indicadores, contexto institucional e fatores determinantes - Sandro Pereira Silva; André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study focuses on the profile of workers' union associations in Brazil given the context of recent changes in the political, economic, social and institutional spheres. More precisely, the objectives were: i) to analytically reconstruct the transformations of trade unionism, internationally and nationally; ii) decompose the variations of the affiliated public according to individual characteristics; and iii) verify the indicators of the probability of adhesion (affiliation) of workers to the unions of their categories in different moments in time. The delimited time horizon of the research was from 2012 to 2022, in order to understand not only the trajectory of union density in Brazil, but also to evaluate possible determinants for the observed results. The results achieved demonstrate the complexity involved around the theme of unionism.
Keywords: J51; J59; J82; L16; 330; Syndicalism; job market; labor regulation; institutional change; sociology of work